Contributions du Laboratoire Conchylicole de Normandie (LCN) au défi MOREST en 2002 - Ropert, Michel; Simonne, Charlotte; Hugonnet, Virginie; Le Gagneur, Eric; Kopp, Joel (2003)
This report present results obtained by the LCN in coastal Ecology of the MOREST program. Most of works presented here have been realised in collaboration with different partners who are cited before each action. This report is divided in 8 parts in 3 themes. WP2 : Characterisation of in-situ summers mortalities • Task 2.2.1. : dynamics of mortality, reproduction and spawning. lntersite comparisons (BASE) • Task 2.2.4 : study of the summer mortalities dynamics of Crassostrea gigas in Bay of Veys (SUMO) WP4 : Experimental tests to cast off summer mortalities problem • Task 4.3.: reduce the critical period before laid: induce oyster laid in the Bay of Veys. • Task 4.4.1.: effects of transfer livestock on summer mortalities : move oysters before the phytoplancton bloom. Delay the introduction date of oyster in the Bay of Veys. WP6 : Coastal ecology and Environmental characterisation • Initial approach of a comparison between Iwo oysters rearing areas : the Bay of Veys (low Normandy) and the Marennes-Oléron Bassin (Charente Maritime from 1997 to 2002b (Unplanned study developed by the LCPC and the LCN) • Shellfish-farming characteristics in the dynamic evolution of the Bay of Veys si nee 10 years (Unplanned study developed by the GEMEL and the LCN) En tant que partenaire du défi MOREST, le LCN a en charge la gestion et la coordination des actions de terrain sur le site atelier de la Baie des Veys. Ce rapport présente l'ensemble des résultats obtenus par le LCN dans le cadre de la thématique "Ecologie Côtière" concernant ce site atelier. La plupart de ces travaux ont été réalisés en étroite collaboration avec différents partenaires qui sont rappelés pour chaque action. Ces dernières se répartissent selon 8 chapitres au sein de 3 thématiques : WP2 : Caractérisation des mortalités estivales in situ • tâche 2.2.1. : dynamique de mortalité, maturation et ponte. Comparaison inter sites (Babe) • tâche 2.2.4 : suivi de la dynamique spatio-temporelle de la mortalité et des performances biologiques de Crassostrea gigas en ...